The biology and ecology of species of Maireana and Enchylaena: intra- and inter-specific competition in plant communities in the eastern goldfields of Western Australia - Jefferson, Lara Vanessa (Curtin University, 2001)
Members of the family Chenopodiaceae are routinely used as colonizer plant species to rehabilitate waste and tailings materials on mine sites in the Eastern Goldfields of Western Australia. These are specifically selected for their salt and drought tolerance and also because they are representative of the surrounding natural vegetation. Where these have been sown, competition between several species has been observed. The resulting plant community structure is typically lower in species diversity than the initial seed mixture. This study aimed to determine whether competition was occurring between five of the species commonly used and some of the mechanisms that determine community structure on the rehabilitated areas of waste material. Atriplex bunburyana, Atriplex codonocarpa, Maireana brevifolia, Maireana georgei and Enchylaena tomentosa were selected for the study, which was conducted in three parts. Firstly, different plant densities and species combinations were studied in the field and in a pot trial to determine whether or not competition was occurring and to determine the resources that the plants were competing for. The results of the field trial revealed that competition was occurring, but that it formed only one component of the complex interactions between plant species, density and soil characteristics (i.e. pH and salinity). The pot trial complemented the outcome of the field trial. In addition, it showed that competition was occurring, but was even more pronounced. This was most likely due to the lack of nutrients and the limited availability of space in the pots.In the second part of this study, the ability of each species to survive and grow when subjected to adverse environmental conditions, such as low moisture availability, high salinity and low light availability, was examined in relation to competition. All five species were treated with different water regimes and soil salinity. Salt played an important role, especially for the Atriplex spp. and M. brevifolia, in ensuring survival when moisture availability was low. The effect of shade on the Maireana species and E. tomentosa was also researched after field observations suggested that M georgei was adversely affected when growing within the canopy of A. bunburyana. The pot trial showed that growth of M. georgei was affected by progressively more shade, whereas E. tomentosa was facilitated by shade. Maireana brevifolia exhibited significant tolerance to low light intensity. In the last part of this three-part study, all five chenopods were screened for allelopathy. Allelopathy may play an important role in determining community structure in successive plant generations. All chenopod species produced allelopathic substances, which were isolated from their leaves. The inhibition of seed germination was found to be speciesspecific and occurred only at certain concentrations. The seed of the Atriplex spp. was not affected by M. georgei and E. tomentosa extracts.